Civil society’s perception of forest ecosystem services. A case study in the Western Alps - Bruzzese, Stefano; Blanc, Simone; Merlino, Valentina Maria; Massaglia, Stefano; Brun, Filippo (Frontiers in Psychology, 2022)
Forest Ecosystem Services (FES) are widely recognised by society nowadays. However, no study in the literature has analysed a ranking of FES after the pandemic. This paper investigated civil society's perception and knowledge towards these services and the presence of patterns of attitude or behaviour regarding their preference. A choice experiment was conducted using the Best-Worst Scaling (BWS) method on a sample of 479 individuals intercepted in the Argentera Valley, in the Western Italian Alps. The results show a strong interest in biodiversity, aesthetic landscape quality and psychophysical health and a lower interest in provisioning services. Based on the individual preferences, civil society can be clustered into five groups for FES, namely "Hedonistic", "Individualist with cultural and health interests", "Sensitive to regulatory and utilitarian functions", "Climate change sensitive" and "Livelihood and hedonistic wellbeing". In general, there is a growing appreciation by civil society for the intangible services offered by the forest, driven by modern lifestyles and an interest in learning more about the services provided. Based on these elements, we believe that similar research should be extended to other mountain contexts to validate the results or find new insights, and that it is now necessary to study how to involve civil society in decision-making processes of forest planning and management at a local level.